Current therapeutic strategies and perspectives in refractory ITP: What have we learned recently? - Lv, Yue; Shi, Huiping; Liu, Hong; Zhou, Lu (Frontiers in Immunology, 2022)
Immune thrombocytopenia (ITP) is an acquired autoimmune bleeding disorder featured by increased platelet destruction and deficient megakaryocyte maturation. First-line treatments include corticosteroids, intravenous immunoglobulin and intravenous anti-D immunoglobulin. Second-line treatments consist of rituximab, thrombopoietin receptor agonists and splenectomy. Although most patients benefit from these treatments, an individualized treatment approach is warranted due to the large heterogeneity among ITP patients. In addition, ITP patients may relapse and there remains a subset of patients who become refractory to treatments. The management of these refractory patients is still a challenge. This review aims to summarize emerging therapeutic approaches for refractory ITP in several categories according to their different targets, including macrophages, platelets/megakaryocytes, T cells, B cells, and endothelial cells. Moreover, current management strategies and combination regimens of refractory ITP are also discussed.